Study of NTF-3 (Neurotrophic Factor 3) Gene Information in Columbidae by In Silico - Suprianto, S.; Budiarsa, I Made; Dhafir, Fatmah; Permatasari, Ni Kadek Dewi; Safitri, Gusti Ayu Kadek Yunita (BERKALA SAINSTEK, 2021)
Neurotrophin Factor 3 (NTF3) is one of the genes that plays an important role in the regulation of the neural systems of vertebrate animals, this gene has a special function in explaining the survival factors of some vertebrate animals. Based on the information obtained from GenBank, the nucleotide sequence of the NTF-3 gene in several vertebrate animals has been known and some of the data obtained have not been studied further for research purposes in adding information related to the molecular character of the NTF-3 gene, such as the NTF-3 gene in Columbidae. Columbidae is a group of birds that have quite diverse species variations, the number of species in columbidae will be very helpful in obtaining data on comparisons of the genetic character of the NTF3 gene. The purpose of this study was to analyze and describe the information on the NTF-3 gene (Neurotrophic Factor 3) in Columbidae through the in silico approach with computational methods. The NTF3 gene nucleotide sequences in Columbidae showed a fairly high level of similarity to the base sequences. This illustrates the fairly close proximity between each species. Geotrygon Montana is a species of Columbidae which has variations of the Base sequence which is quite different from other species. Evaluation of the model structure shows good stability of each target protein, all evaluation results describe a good structure, meaning that the conformation of each target sequence is in accordance with the sequence, so that the structure that is built has high accuracy with the actual model. The results of this research study can be a special description in explaining the genetic characteristics of several Columbidae species for the purposes of conservation measures or efforts to preserve Columbidae species at the molecular and population genetic levels.